IDENTIFIKASI JENIS POHON SARANG DAN PAKAN ORANGUTAN (Pongo pygmaeus) DI ARBORETUM NYARU MENTENG, PALANGKA RAYA (Identification of Trees as Nest and Food of Orangutan (Pongo pygmaeus) at the Arboretum of Nyaru Menteng, Palangka Raya) : Fouad Fauzi1,2, Penyang1,2, Nisfiatul Hidayat1 - Admin JHT (Jurnal Hutan Tropika, 2017)
ABSTRACT This research was aimed to know some trees that used to nest and food of orang utan (Pongo pygmaeus) at the arboretum of Nyaru Menteng in Palangka Raya City. Analysis of vegetation using Point Centered Quarter Method with 23 sample points at the field. Collected data at the August 2017 were founded 25 species of trees, from16 family, whereas 17 trees were used as nest and food and 8 trees were used as nest only. The distance between each tree to measuring point was 3,71 m. Density of the trees namely 726 trees ha-1, with domination namely 28.37, frequency namely 3.48. The important value index of hangkang (Palaquium leiocarpum) was highest, namely 51.91%. Summed dominance ratio namely 17.3 %. Diversity index was moderate with value namely 2.81. Evenness index was high with value namely 0.87. Keywords: Food, nest, Nyaru Menteng, Pongo pygmaeus